Smart nutrient management practices for sustainable crop production - Meena, B. P.; Yadav, D. K.; Shirale, A. O.; Rani, Khusbhoo; Behera, S. K.; Mohanty, M. (Indian Farming, 2025)
Global food security faces pressure from rising population, climate change, and shrinking natural resources. In India, the second-largest fertilizer consumer after China, fertilizers contribute ~40–50% of yield gains, making nutrient management essential. Yet, inefficient use results in poor utilization efficiencies i.e. 30–50% for nitrogen, 15–20% for phosphorus, 50–80% for potassium, and